'Upstart Crow'? The Myth of Shakespeare's Plagiarism. (28th September 2016) - Vickers, Brian
Abstract : In his deathbed pamphlet Greenes Groatsworth of Wit, bought with a Million of Repentance (1592), Robert Greene warned his fellow playwrights to beware of the actors, 'those Puppets (I meane) that spake from our mouths, those Anticks garnisht in our colours', and especially 'an upstart Crow, beautified with our feathers' who 'is in his own conceit the only Shake-scene in a countrey.' In 1787 Edmond Malone took this to be an accusation of plagiarism, and used it to justify his theory that Greene had written the unauthorized Quartos, The First Part of the Contention (1594) and The True Tragedie of Richard Duke of York (1595), and that Shakespeare 'new-modelled and amplified these two pieces' to create what the 1623 Folio calls The Second and Third Part of King Henry VI, without acknowledging his debt, thus arousing Greene's anger. Malone had no evidence for this theory, and it was comprehensively demolished by Peter Alexander in 1929 and by H. O. White in 1935. Despite their work, John Dover Wilson revived Malone's theory in 1951, and it continues to produce claims that Shakespeare was a plagiarist. This essay examines all the writings of Greene in which he criticizes the actors, showing that he repeats over and again, in very similar terms, the same basic accusation that they depend on the playwrights yet unjustly enjoy more prestige and financial reward. Greene never accused Shakespeare of plagiarism.